Precise predictions for Wγγ+jet production at hadron colliders - Campanario Pallás, Francisco; Englert, Christoph; Rauch, Michael; Zeppenfeld, Dieter (Physics letters, 2011)
In this Letter we report on a calculation of W±γγ+jet production at next-to-leading order QCD. We include the leptonic decays of the W and take into account all off-shell and finite width effects. This is the first computation which falls into the category of triboson+jet production at next-to-leading order QCD. In total we find sizable corrections with non-trivial phase space dependencies. Therefore, our results are important for phenomenological analyses such as the extraction of anomalous electroweak quartic couplings from inclusive hadron collider data.
Gesehen am 27.06.2022